Too Informal? How a Chatbot’s Communication Style Affects Brand Attitude and Quality of Interaction - Liebrecht, Christine; Sanders, Lena; van Hooijdonk, C.M.J. (Springer, 2021)
This study investigated the effects of (in)formal chatbot responses and brand familiarity on social presence, appropriateness, brand attitude, and quality of interaction. An online experiment using a 2 (Communication Style: Informal vs. Formal) by 2 (Brand: Familiar vs. Unfamiliar) between subject design was conducted in which participants performed customer service tasks with the assistance of chatbots developed for the study. Subsequently, they filled out an online questionnaire. An indirect effect of communication style on brand attitude and quality of interaction through social presence was found. Thus, a chatbot’s informal communication style induced a higher perceived social presence which in turn positively influenced quality of the interaction and brand attitude. However, brand familiarity did not enhance perceptions of appropriateness, indicating participants do not assign different roles to chatbots as communication partner.
Keywords: Brand familiarity; Chatbots; Communication style; Conversational human voice; Social presence; Taverne; Theoretical Computer Science; General Computer Science